PENGARUH MOTIVASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Suryadewi, Made Dani; Sintaasih, Desak Ketut; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 9 No 9 (2020)DO - 10.24843/EJMUNUD.2020.v09.i09.p04, 2020)
The purpose of this study was to determine the effect of motivation, compensation and work discipline on employee work productivity. This research was conducted at PT. Lila Buana Wisata where the company is engaged in travel services located in Renon, Denpasar and Tuban, Badung. The population in this study as many as 35 people using saturated sampling techniques, the sample used is the entire population of 35 people. The data analysis technique used is multiple linear regression. Based on the results of data analysis, it was found that motivation has a positive and significant effect on work productivity. Compensation also has a positive and significant effect on work productivity. Similarly, work discipline is proven to have a positive and significant effect on work productivity. To increase employee productivity, the company should continuously motivate employees, provide compensation in accordance with the workload of employees and enforce employee discipline so that work productivity continues to increase so that the company is able to compete and the company's survival is guaranteed. Keywords : work productivity, motivation, compensation, work discipline